Inaugural central fueling experiment with Compact Torus in EAST - Y. Ye; D.F. Kong; M.S. Tan; F.B. Zhong; C.M. Qu; X.P. Wang; Z.H. Zhao; L.X. Yang; Z.X. Li; Y.H. Wu; B. Cao; H.L. Zhao; et al. (Nuclear Fusion, 2025)
We report, for the first time, non-disruptive central fueling experiments utilizing Compact Torus (CT) plasma injection in the medium-sized fully-superconducting tokamak, EAST ( R _0 = 1.9 m, a = 0.45 m, B _t = 1.5–2.5 T). In these experiments, the CT plasma achieved velocities near 150 km s ^−1 , with electron densities of 1.6 × 10 ^22 m ^−3 and particle numbers reaching 1.3 × 10 ^20 . After traversing approximately 1300 mm through the drift tube, the CT plasma was successfully injected into the normalized poloidal flux surface at Ψ _N = 0.8–0.85, corresponding to a magnetic field strength of 2.05–2.02 T. This direct injection depth exceeds predictions from empirical formulas and represents the highest magnetic field strength at which CT injection has been demonstrated to date. Following the direct injection, CT particles underwent further indirect inward diffusion toward the core region. Density measurements revealed that CT deposition disrupted the density profile in the core of the tokamak, resulting in a hollow distribution that ultimately evolved into a more peaked density profile. These findings have important implications for improving plasma confinement in tokamaks.